2021
DOI: 10.1542/hpeds.2021-006037
|View full text |Cite
|
Sign up to set email alerts
|

Choosing Wisely in Pediatric Hospital Medicine: 5 New Recommendations to Improve Value

Abstract: OBJECTIVES The health care system faces ongoing challenges due to low-value care. Building on the first pediatric hospital medicine contribution to the American Board of Internal Medicine Foundation Choosing Wisely Campaign, a working group was convened to identify additional priorities for improving health care value for hospitalized children. METHODS A study team composed of nominees from national pediatric medical professi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 111 publications
1
11
0
Order By: Relevance
“…Finally, in 2021, Tchou et al provided a timely and extensive update to the 2013 CW list for pediatric hospital medicine: they produced and published the last 5 highest-scoring American pediatric recommendations, using a structured approach, with a focus on specific aspects of hospital care such as the length of intravenous antibiotic therapy, the length of stay for febrile infants evaluated for severe bacterial infection, the threshold of phototherapy for neonatal hyperbilirubinemia, the use of narrow-spectrum antibiotic therapy for community-acquired pneumonia, and the appropriateness of intravenous antibiotics in infants with maternal risk factors for sepsis ( Supplementary Table S2 ) ( 13 ).…”
Section: Narrative Review Of Choosing Wisely In Pediatric Healthcarementioning
confidence: 99%
“…Finally, in 2021, Tchou et al provided a timely and extensive update to the 2013 CW list for pediatric hospital medicine: they produced and published the last 5 highest-scoring American pediatric recommendations, using a structured approach, with a focus on specific aspects of hospital care such as the length of intravenous antibiotic therapy, the length of stay for febrile infants evaluated for severe bacterial infection, the threshold of phototherapy for neonatal hyperbilirubinemia, the use of narrow-spectrum antibiotic therapy for community-acquired pneumonia, and the appropriateness of intravenous antibiotics in infants with maternal risk factors for sepsis ( Supplementary Table S2 ) ( 13 ).…”
Section: Narrative Review Of Choosing Wisely In Pediatric Healthcarementioning
confidence: 99%
“…Barriers to the identification of low-value care were discussed in four records,15 19 42 57 enablers in three records10 42 45 and other contextual factors in two records 15 41. Some contextual factors aligned with the four factors driving overuse that were used for the framework synthesis 19.…”
Section: Resultsmentioning
confidence: 99%
“…A diverse range of clinical settings were targeted, spanning specific wards or services through to whole of hospital, health system and global approaches. Three of 27 studies targeted paediatric hospitals or health services specifically 40–42. The entire continuum of care (primary care to specialist care or healthcare system) was covered by six records 19 43–47.…”
Section: Resultsmentioning
confidence: 99%
“…41 Prior studies also examined interhospital variation in disease prevalence and costs, emphasizing the need for standardization of high-value, quality care across children's hospitals through evidence-based quality improvement initiatives. [42][43][44][45] Measures taken to mitigate high costs at children's hospitals include more conscientious utilization of low-value services, with decrease in duration of intravenous antibiotic therapy, reduction in laboratory tests, and use of X-rays. 27,44,46 Additionally, with increased use of telemedicine in the setting of the COVID-19 pandemic, a single institution study demonstrated that surgical specialty telehealth visits are associated with lower hospital charges compared with in-person encounters, though reimbursements were not significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44][45] Measures taken to mitigate high costs at children's hospitals include more conscientious utilization of low-value services, with decrease in duration of intravenous antibiotic therapy, reduction in laboratory tests, and use of X-rays. 27,44,46 Additionally, with increased use of telemedicine in the setting of the COVID-19 pandemic, a single institution study demonstrated that surgical specialty telehealth visits are associated with lower hospital charges compared with in-person encounters, though reimbursements were not significantly different. 47 The introduction of evidence-based clinical care and/or enhanced recovery after surgery protocols for common surgical procedures such as cleft palate repair, appendicitis, and blunt abdominal trauma have also effectively decreased length of stay and costs.…”
Section: Discussionmentioning
confidence: 99%